Rational Thinking Promotes Suspect‐friendly Legal Decision Making. Issue 3 (17th November 2015) - Rassin, Eric
Summary: Judges, juries, and other legal decision makers are frequently obligated to find facts about an alleged crime. Does this fact finding benefit from purely rational decision making or from a more intuitive approach? In three studies, rationality was found to be related to more suspect‐lenient decision making. The data suggest that fact finding in criminal proceedings is served best with strictly rational analyses of the evidence, rather than with intuition, gut feeling, and other obscure decision processes.Copyright © 2015 John Wiley & Sons, Ltd.